HUBUNGAN INISIASI MENYUSU DINI (IMD) DAN PEMBERIAN AIR SUSU IBU (ASI) EKSKLUSIF DI RSUD WANGAYA KOTA DENPASAR - Jessica Irawan (Poltekkes Kemenkes Denpasar, 2018)
Abstract. Immediate breastfeeding indeed has positive impacts for both mother and baby. Based on Fika’s and Syafiq’s research, a mother who does immediate breastfeeding has 2-8x higher chance in giving exclusive breastfeeding. The purpose of this research is to understand the relationship between immediate breastfeeding and exclusive breastfeeding at Kaswari Ward Wangaya Hospital, Denpasar City. For this research, we used analytic approach with case control as the study design. Population that we use was mothers who have 7-12 months old baby in Kaswari Ward Wangaya Hospital, Denpasar City. Sampling was done through purposive sampling method, with the sample of 50 mothers. Whereas, data analysis was done by using chi square method. The result of this research shows that there was positive correlation between the practice of immediate breastfeeding and giving exclusive breastfeeding (p value=0,04). Thus, mother who practices immediate breastfeeding has 5x higher opportunity to give exclusive breastfeeding.Keywords: Immidiate Breastfeeding, Exclusive Breastfeeding, The mothers Group Who Gets Health Services at Wangaya Hospital